2019
DOI: 10.3390/coatings9050308
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Versus Polycrystalline Shape Memory Cu-Al-Ni Thin Films

Abstract: In this work, two different approaches were followed to obtain Cu-Al-Ni thin films with shape memory potential. On the one hand, Cu-Ni/Al multilayers were grown by magnetron sputtering at room temperature. To promote diffusion and martensitic/austenitic phase transformation, the multilayers were subjected to subsequent heat treatment at 800 °C and quenched in iced water. On the other hand, Cu, Al, and Ni were co-sputtered onto heated MgO (001) substrates held at 700 °C. Energy-dispersive X-ray spectroscopy, X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…High-throughput combinatorial thin films production [ 31 , 32 ] was developed to optimize the required concentration in ternary and quaternary alloys based on the TiNi system [ 33 , 34 ]. In contrast to the hundreds of publications on TiNi SMA thin films [ 17 , 18 , 26 , 27 ], only a few works have been devoted to producing and characterizing Cu-based SMA thin films [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Nevertheless, recent studies have shown that at the micro- and nanoscales [ 44 , 45 ], Cu-Al-Ni SMA exhibits shape memory and superelastic behavior superior to those of Ti-Ni, with excellent cycling behavior at these small scales [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput combinatorial thin films production [ 31 , 32 ] was developed to optimize the required concentration in ternary and quaternary alloys based on the TiNi system [ 33 , 34 ]. In contrast to the hundreds of publications on TiNi SMA thin films [ 17 , 18 , 26 , 27 ], only a few works have been devoted to producing and characterizing Cu-based SMA thin films [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Nevertheless, recent studies have shown that at the micro- and nanoscales [ 44 , 45 ], Cu-Al-Ni SMA exhibits shape memory and superelastic behavior superior to those of Ti-Ni, with excellent cycling behavior at these small scales [ 46 ].…”
Section: Introductionmentioning
confidence: 99%